Reducing the Environmental Impact of Dietary Choice: Perspectives from a Behavioural and Social Change Approach - Joyce, A.; Dixon, Sarah; Comfort, Jude; Hallett, Jonathan (Hindawi Publishing Corporation, 2012)
Climate change is recognised as a significant public health issue that will impact on food security. One of the major contributors to global warming is the livestock industry, and, relative to plant-based agriculture, meat production has a much higher environmental impact in relation to freshwater use, amount of land required, and waste products generated. Promoting increased consumption of plant-based foods is a recommended strategy to reduce human impact on the environment and is also now recognised as a potential strategy to reduce the high rates of some chronic diseases such as cardiovascular disease and certain cancers. Currently there is a scant evidence base for policies and programs aiming to increase consumption of plant-based diets and little research on the necessary conditions for that change to occur and the processes involved in such a change. This paper reviews some of the environmental and health consequences of current dietary practices, reviews literature on the determinants of consuming a plant-based diet, and provides recommendations for further research in this area.